2011
DOI: 10.5505/tatd.2011.90377
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of non-thromboembolic findings encountered in multidetector computed tomography pulmonary angiography studies in patients with suspected pulmonary embolism

Abstract: ÖZET AmaçPulmoner emboli ön tanısı ile çok kesitli bilgisayarlı tomografi (ÇKBT) pulmoner anjiyografi tetkiki yapılan olgularda pulmoner emboli sıklığının belirlenmesi ve emboli saptanmayan olgularda tanı ve tedaviye katkı sağlayan diğer bulguların analiz edilmesidir. Gereç ve YöntemBu geriye dönük çalışma için onay hastanemizin yerel etik kurulundan alındı. Çalışmaya pulmoner emboli ön tanısı ile Aralık 2009 -Kasım 2010 tarihleri arasında ÇKBT pulmoner anjiyografi tetkiki yapılan 223 olgu (128 erkek, 95 kadın… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Again, that study reported findings that were both related to patient's signs and symptoms (62.5%) and were only incidental pathologies (37.5%). MSCT could not detect any abnormality in 43 (21.8%) cases (22). Richman et al researched 1025 patients who had suspected PE and found that 104 patients had PE and 921 patients had no PE.…”
Section: Discussionmentioning
confidence: 99%
“…Again, that study reported findings that were both related to patient's signs and symptoms (62.5%) and were only incidental pathologies (37.5%). MSCT could not detect any abnormality in 43 (21.8%) cases (22). Richman et al researched 1025 patients who had suspected PE and found that 104 patients had PE and 921 patients had no PE.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of PTE can be masked by comorbidities (4). Invasive pulmonary angiography has been accepted as the gold standard for the diagnosis of PTE; however, its use is limited due to its high mortality rate (0.5%), invasiveness, expense and requirement for specialized infrastructure that may not be available in all centers (5).…”
Section: Introductionmentioning
confidence: 99%
“…1 Clinically, PE ranges from anatomically small and clinically asymptomatic emboli to massive proximal emboli with cardiogenic shock. 2,3 Since early treatment is vital, immediate and correct diagnosis is important. 4 Helical computed tomography (CT) of the pulmonary arteries has become the first-line technique for the detection of emboli in the large and segmental vessels.…”
mentioning
confidence: 99%
“…4 Helical computed tomography (CT) of the pulmonary arteries has become the first-line technique for the detection of emboli in the large and segmental vessels. 3,5,6 The European Society of Cardiology recently included computed tomography pulmonary angiography (CTPA) as the reference standard modality to be used following initial clinical evaluation. 7 PE is diagnosed by demonstrating a filling defect in the pulmonary arteries.…”
mentioning
confidence: 99%